Tanzanian gut microbiota profiles linked to high but rapidly waning yellow fever antibody titers - Jeremia J. Pyuza; Marloes M. A. R. van Dorst; David Barnett; Koen Stam; Mikhael Manurung; Linda Wammes; Marion König; Yvonne Kruize; Nikuntufya Andongolile; Anastazia Ngowi; Elichilia R. Shao; Vesla I. Kullaya; et al. (npj Biofilms and Microbiomes)
Abstract Vaccine responses vary across populations and are influenced by numerous intrinsic and extrinsic factors, including the gut microbiota. However, studies linking microbiota composition to vaccine immunogenicity in low- and middle-income countries are sparse. In this study, we examined the gut microbiota of 143 healthy rural and urban living Tanzanians who participated in a yellow fever vaccine (YF-17D) trial. We found significant differences in gut microbiota profiles between rural and urban participants. Rural-associated microbiota showed higher diversity and enrichment of taxa like Prevotella and Succinivibrio, which were linked to dietary intake patterns. Yellow fever neutralizing antibody titers were higher in rural compared to urban participants. Interestingly, a subset of urban individuals with a rural-like microbiota had higher antibody titers and faster antibody waning than those with a more industrialized microbiota. These findings suggest that gut microbiota composition might be linked to vaccine immunogenicity, potentially outweighing the influence of living location.